Possible causes of pain syndrome development in the right hypochondrium: in the focus of opistorchosis - Dmitry I. Trukhan; Mariya Yu. Rozhkova; Dar'ya S. Ivanova; Larisa Yu. Trukhan; Viktoriia V. Goloshubina; Nataliya V. Bagisheva (LLC "MEDIAFORMAT", 2021)
In real clinical practice, the therapist and general practitioner often have to deal with the "right hypochondrium syndrome". One of the possible reasons for the development of "right hypochondrium syndrome" is opistorchosis. Opistorchosis is a natural focal anthropozoonosis caused by the trematode Opisthorchis felineus, which is characterized by the involvement in the parasitic process, along with the parasite habitat, of the most important functional systems of the body with a latent or clinically manifest course in the acute and chronic stages, with various variants of their manifestations. Opistorchosis from an endemic regional pathology, due to the active migration of the population in modern Russia, is becoming a general problem that doctors in any region of the country may face in their practice today. The current aspects of the clinic and diagnosis of opistorchosis are considered. In the conclusion, 2 clinical examples are given that demonstrate the advisability of considering opistorchosis as a possible cause of the development of "right hypochondrium syndrome" when conducting differential diagnostics in both endemic and non-endemic regions for opistorchosis.